Cryptosporidium and Giardia infection and drinking water sources among children in Lege Dini, Ethiopia - Ayalew, D.; Boelee, Eline; Endeshaw, T.; Petros, B. (2008)
We assessed the prevalence of Cryptosporidium and Giardia infections among children using protected and unprotected water sources in the Lege Dini watershed, Eastern Ethiopia, in November 2005 and May 2006. Of 655 children examined, 80 (12.2%) were infected with Cryptosporidium and 231 (35.3%) with Giardia. No difference was observed in the prevalence of cryptosporidiosis and giardiasis (P > 0.05) between children drinking water from protected and unprotected sources.